2015
DOI: 10.1080/15384101.2015.1046655
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the stability and localization of CDK inhibitor p27Kip1 via CSN6-COP1 axis

Abstract: The COP9 signalosome subunit 6 (CSN6), which is involved in ubiquitin-mediated protein degradation, is overexpressed in many types of cancer. CSN6 is critical in causing p53 degradation and malignancy, but its target in cell cycle progression is not fully characterized. Constitutive photomorphogenic 1 (COP1) is an E3 ubiquitin ligase associating with COP9 signalosome to regulate important target proteins for cell growth. p27 is a critical G1 CDK inhibitor involved in cell cycle regulation, but its upstream reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…Thus, we performed ubiquitination assay and found that CSN6 overexpression did not increase the endogenous ubiquitination level of p16 ( Figure 5A ). The COP9 signalosome usually collaborates with an E3 ligase such as SKP2 or COP1 to degrade target proteins through ubiquitination 30,31 . We then examined whether CSN6 reduced the expression of p16 through E3 ubiquitin ligases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we performed ubiquitination assay and found that CSN6 overexpression did not increase the endogenous ubiquitination level of p16 ( Figure 5A ). The COP9 signalosome usually collaborates with an E3 ligase such as SKP2 or COP1 to degrade target proteins through ubiquitination 30,31 . We then examined whether CSN6 reduced the expression of p16 through E3 ubiquitin ligases.…”
Section: Resultsmentioning
confidence: 99%
“…In the ubiquitination pathway, ubiquitin is activated in a two-step reaction by an E1 ubiquitin-activating enzyme. Then GC cells were treated with PYR-41 (an ubiquitin E1 inhibitor), and the results showed that p27 which is identified to be degraded by ubiquitination 31 , was upregulated with the inhibition of E1 activity. However, p16 did not change when the E1 activity was inhibited ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical analyses were carried out using IBM SPSS statistics 19 and GraphPad Prism 6. The Pearson's Х 2 test was used to determine the correlations between protein expression and clinical variables.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, both CSN5 and CSN6 was identified as a c-Jun activator (16,17). CSN5 and CSN6 are capable of inducing degradation of cyclin-dependent kinase inhibitor p27Kip1 and p57Kip2 (14,15,18,19). Furthermore, CSN5 and CSN6 facilitate degradation of p53 via stabilization of MDM2 (11,20).…”
Section: Introductionmentioning
confidence: 99%